Supporting Workplace Detachment and Reattachment with Conversational Intelligence - Williams, Alex; Kaur, Harmanpreet; Mark, Gloria; Thompson, Anne Loomis; Iqbal, Shamsi; Teevan, Jaime (2018 ACM Conference on Human Factors in Computing Systems (CHI '18), 2018)
Research has shown that productivity is mediated by an individual’s ability to detach from their work at the end of the day and reattach with it when they return the next day. In this paper we explore the extent to which structured dialogues, focused on individuals’ work-related tasks or emotions, can help them with the detachment and reattachment processes. Our inquiry is driven with SwitchBot, a conversational bot which engages with workers at the start and end of their work day. After preliminarily validating the design of a detachment and reattachment dialogue framework with 108 crowdworkers, we study SwitchBot’s use in-situ for 14 days with 34 information workers. We find that workers send fewer e-mails after work hours and spend a larger percentage of their first hour at work using productivity applications than they normally would when using SwitchBot. Further, we find that productivity gains were better sustained when conversations focused on work-related emotions. Our results suggest that conversational bots can be effective tools for aiding workplace detachment and reattachment and help people make successful use of their time on and off the job.